Stochastic damage model for bond stress-slip relationship of reinforcing bar embedded in concrete. (1st September 2019) - Huang, Le; Ye, Hailong; Chu, Shaohua; Xu, Lihua; Chi, Yin
Highlights: A stochastic damage model based on an innovative spring system is proposed. A random variable that specifies the failure displacement of micro spring elements is suggested. The path-dependence and pressure-sensitivity of bond response are discussed. Abstract: The bond behavior of reinforcing bars embedded in concrete has been widely evidenced to exhibit an obvious nonlinearity with a high degree of randomness. To cope with this phenomenon, a stochastic damage model based on an innovative spring system is proposed in this paper. To describe the stochastic feature of bond response, the model introduces a random variable that specifies the failure displacement of micro spring elements, and meanwhile, two evolution laws for the interfacial damage and sliding are also defined respectively. Moreover, the effects of loading history and lateral stress are incorporated into the model, which is capable of reproducing the path-dependence and pressure-sensitivity of bond behavior faithfully. Finally, the model is numerically implemented by exploiting an implicit backward Euler scheme and verified by a number of numerical trial tests and independent experimental results. The satisfactory validations may provide a beneficial reference to bring the stochastic nature of nonlinear interfacial debonding into future theoretical studies on the structural response of reinforced concrete structures.